Development of q-switched and modelocked erbium-doped fiber lasers (EDFL) based on gold nanoparticles (GNP) as saturable absorber / Nursyazana Zainal Abidin - Nursyazana , Zainal Abidin (2019)
In this experiment, we experimentally demonstrate a Q-switched and mode-locked Erbium-doped fiber lasers (EDFLs) using gold nanoparticle (GNPs) which is embedded into a polyvinyl alcohol (PVA) film as a passive saturable absorber (SA). The film is sandwiched between two ferrules via a fiber connector to form a fiber-compatible SA and integrated into the laser cavity for Q-switching and mode locking pulse generation in a 14.8m cavity length. The laser produces a successful stable q-switched pulse train operating at 1564.2nm within the incident pump power ranging from 63.4mW to 92.3mW. The achieved repetition rate ranges from 49.4kHz to 56.8kHz and the pulse width can be as narrow as 4.16μs. A 200-m long standard single mode fiber (SMF) is added to the cavity to achieve stable mode-lock nanosecond pulses at 1567nm with spectral width of 1.1nm. Furthermore, a pulse duration of 450ns and a repetition rate of 970kHz is achieved. The average output power is 2.48mW, which corresponds to a single pulse energy of 25.5nJ at pump power of 187mW.